The Importance of Decision Making for Information and Library Managers - Jumino Jumino (Anuva: Jurnal Kajian Budaya, Perpustakaan, dan Informasi, 2018)
This articles deals with the importance of decision making done by Information and Library Managers. The method used is document study with qualitative approach. The results of the analysis show that decision making for Information and Library Managers are an essential function in managing libary and information service. It is the primary task of Information and Library Managers, since every function of management a library needs a decision to be applied. It involves the stages of decision making process, such as defining objectives, collecting information, choosing and discussing alternatives, implementing decisions, delegating jobs, and evaluating them. Furthermore, there two types of Information and Library Managers, rational and irrationa[ managers. Rational managers worked with their subordinates in group, delegated to their subordinates, and the final decision belonged to the subordinates. On the other hand, in planning and solving problems dealing with decision making proccess, the irrational manager never involved and communicated with subodinates at all.